TAFSIR AYAT-AYAT NEUROSAINS DAN IMPLIKASINYA BAGI PENGEMBANGAN HIGHER ORDER THINKING (HOT) DALAM PENDIDIKAN ISLAM - Wikanti Iffah Juliani; Addinia Rizki Sabili; Suyadi Suyadi (MUADDIB Jurnal Kependidikan dan Keislaman, 2020)
AbstractHumans are equipped with a mind that distinguishes their position from other creatures and the potential to distinguish between good and bad. The concept of reason in the sphere of tadabbur, tafakkur, and tadzakkur is in line with neuroscience as the study of brain activity. The concept of reason is full of scientific values. With reason, humans think to be able to capture the essence behind a sign so that their faith and faith will increase.The purpose of this article is to interpret verses about neuroscience and their implications for the development of critical thinking in Islamic education. The method of interpretation uses the maudhu'i approach, which is to collect Qur'anic verses about neuroscience with their explanations and explanations. The results of the interpretation show that human reason can be developed in its potential through the concept of critical thinking. This concept is derived in the form of Higher Order Thinking (HOT) in the world of education as an implication of the creation of reason. Especially in Islamic education this can optimize the acquisition of knowledge and shape the character of man himself.